Promoting Religious Moderation through English Language Teaching: Strategies and Challenges in Islamic Educational Settings - Umar; Muhammad Aulia Taufiqi; M Bambang Purwanto (ETERNAL (English Teaching Journal), 2024)
Religious moderation aligns with the principles of sustainable development by fostering a culture of peace, justice, and inclusivity. Islamic educational settings often integrate religious values into the ELT curriculum, incorporating Islamic stories, teachings, and ethical principles into language learning materials and activities. By using this methodological approach, this research aims to provide valuable insights into effective strategies and key challenges in encouraging religious moderation through ELT in an Islamic education environment. The data used in this research were interview transcripts, focus group recordings, and documents which were then analyzed using thematic analysis to identify recurring themes, patterns, and insights related to strategies and challenges in encouraging religious moderation through ELT. This study adopted a qualitative research design to explore the various experiences, perspectives and practices of educators and stakeholders regarding the promotion of religious moderation through ELT. The study identified some strategies for promoting religious moderation: Incorporate Multicultural Content; Encourage Critical Thinking; Facilitate Open Dialogue; Promote Empathy and Respect; Address Misconceptions and Stereotypes; Highlight Common Values; Engage with Religious Leaders and Community Members and Empower Educators with Training. Some challenges as well were also found: Sensitivity and Cultural Context; Resistance to Change; Misinformation and Stereotypes; Balancing Academic Freedom and Sensitivity; Language Barriers; Lack of Resources and Training; Community and Parental Concerns; and Political and Social Context.